Streamlining Space Processes through IT Automation: Reducing Manual Tasks for Enhanced Efficiency in Space Exploration - Choudhary, Anupama; Jain, Vinita (International Journal of Psychosocial Rehabilitation, 2025)
This research paper explores the integration of Information Technology (IT) automation in the space industry to streamline processes and reduce manual tasks. As space exploration advances, the complexity of missions and the vast amount of data generated necessitate efficient and reliable systems. Automation еmеrgеs as a key solution to enhance the efficiency, accuracy, and overall success of space endeavors. This paper examines various applications of IT automation in space processes, including data processing, mission planning, maintenance, communication, and security. By leveraging automation, space agencies can optimize resource utilization, minimize errors, and focus human efforts on complex tasks. The study reviews existing implementations, challenges, and potential future developments in IT automation for space exploration. The background section provides an overview of the evolution of space exploration and the challenges posed by manual-intensive processes. It highlights the growing nееd for automation to address these challenges, emphasizing the role of IT in transforming space operations Each subsection explores the benefits, challenges, and potential advancements in implementing automation in these areas. This section provides real-world examples of IT automation in space exploration. Case studies include successful implementations, lessons learned, and the impact on mission outcomes. Examining these cases offers insights into the practical application of automation technologies. Despite its numerous advantages, the implementation of IT automation in space processes comes with challenges. This section addresses issues such as system reliability, cybersecurity, ethical considerations, and the adaptability of automation to evolving mission requirements. Anticipating the future of IT automation in space exploration, this section discusses potential advancements, merging technologies, and areas for further research. It explores how automation can adapt to future challenges and contribute to the evolution of space exploration.